Rủi ro địa chính trị và thị trường chứng khoán các nước ASEAN-6 - Ngô Thái, Hưng; Bùi Minh , Bảo (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study examines the lead-lag relationship between global geopolitical risks (GPR) and ASEAN-6 stock markets utilizing wavelet analysis and the spectral Granger causality during the period 2018–2023 in time-frequency space. Our results reveal the existence of a lead-lag nexus between the two variables in the short and medium run, which implies that GPR has a significant impact on ASEAN stock markets. In addition, there is a bidirectional causality between GPR and ASEAN stock markets, depending on timescales and periods. Furthermore, during the COVID-19 and Ukraine-Russia crises, we find a short-run negative association leading from the GPR to stock markets. These outcomes may have implications for investors, and policymakers, and they may help them better understand how the stock market operates during times of acute market stress.
Keywords: Geopolitical Risks; ASEAN Stock Markets; Wavelet Analysis